Analisis Item Dalam Pembuatan Tes - Sukoco - Universitas Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2008)
AbstractMen accessories can not be measured directly. To measure one’s competence it is needed an instrument, namely, test. Test consists of some items which each item describe every indicator. The indicators will make one’s competence. To make good test there must be item analysis that constructs it. There are two theories to analyze item, they are Classical Test Theory (CTT) and Item Response Theory (IRT). Item statistic on CTT are mostly used in selecting items, while item parameters on IRT are used in judging respondent scores, calibration, and equating test. The benefit of the parameters on IRT can be used on the adaptive test that is conducted by computer, bias study, and test equation. Keywords: Item analysis, test construction,  clasical tes teory, modern test theory